"His dominion" and the "yellow peril": Protestant missions to the Chinese immigrants in Canada, 1859-1967. - Wang, Jiwu. (University of Ottawa (Canada), 2000)
This is a historical study of Protestant missions to the Chinese immigrants in Canada from 1859 to 1967. It will describe and analyze, against the relevant historical background, Protestant clergy's attitudes to the Chinese, the motivation that led them to work among the Chinese, and the activities and results of the missions. It will also analyze the Chinese response to the missions, and the impact of the missions on Chinese immigrants' lives in Canada. The consensus of wanting to keep Canada's white Anglo-Saxon heritage provided the Canadian Protestant churches with a strong impetus to instill into all other ethnic groups the ideals and standards of white Anglo-Saxon Protestantism. Thus, the history of Protestant missions to the Chinese immigrants in Canada is also the history of the encounter between two different cultures and the history of a minority group's survival in a hostile society. In this sense, this history goes beyond the Chinese context and includes the interethnic relations with the dominant white English-speaking group.
Keywords: Religion, History of.